THE EFFECTIVENESS TEST OF ALOE VERA EXTRACT INHIBITING THE GROWTH OF STAPHYLOCOCCUS AUREUS BACTERIA - Nurhidayanti Nurhidayanti (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2022)
Staphylococcus aureus bacteria are resistant to several kinds of antibiotics, so there is a need for natural antibiotics derived from plants, namely aloe vera. The objective of this study was to determine the effect of aloe vera leaf extract in inhibiting the growth of Staphylococcus aureus bacteria. The type of research used was experimental using the disc diffusion method with a total of 25 samples with five concentrations of 20%, 40%, 60%, 80% and 100% then the data were analyzed using the One Way ANOVA test. The result is that aloe vera extract can inhibit the growth of Staphylococcus aureus bacteria, it is proven by the presence of a disc zone at 100% concentration with a diameter of 11.5 mm. The results of statistical analysis with the One Way ANOVA test, in a value of 0.000, meaning that there was a significant difference. The conclusion obtained is that aloe vera extract can slow down the growth of Staphylococcus aureus bacteria but based on the standard value of sensitivity of an aloe vera extract bacteria with the highest concentration it cannot be used as an antibiotic because it is less than the standard value of 14 mm.